A 2-Week Specific Volleyball Training Supported by the Whole Body Cryostimulation Protocol Induced an Increase of Growth Factors and Counteracted Deterioration of Physical Performance - Jaworska, Joanna; Micielska, Katarzyna; Kozłowska, Marta; Wnorowski, Krzysztof; Skrobecki, Jerzy; Radzimiński, Lukasz; Babińska, Anna; Rodziewicz, Ewa; Lombardi, Giovanni; Ziemann, Ewa (Frontiers in Physiology, 2018)
Potentially beneficial effects of cold therapies on training adaptation still remain unequivocal. We have, thus, decided to evaluate the effects of a 2-week volleyball training program supported by 10 sessions of whole body cryostimulation (WBC) on growth factors and physical performance. Twenty healthy college-aged men and women randomly assigned either to the cryostimulation group (CRY) or the control group (CON; executed passive rest). Both groups took part in the same 2-weeks training program. Additionally, the CRY group attended in 10 cryo-sessions (3 min, -110°C temperature, five times/week). Blood samples were collected at baseline, 1 h after the first cryo-session as well as before and 1 h after the last session of WBC to assess growth factors, myokines concentration and the amino acid profile. Motor abilities were tested before commencing the training program and 2 days after its completion. The applied intervention resulted in an increase of brain-derived neurotrophic factor and insulin-like growth factor 1 concentrations. The adjusted effect describing the difference between groups in response to applied procedures was for both growth factors large and very likely in the CRY, higher than in the CON group (113%; Coefficient Interval: 38–230%, 45%; Coefficient Interval: 17–79%, respectively). Physical performance dropped in both groups, yet in the CRY group, the magnitude of change was smaller. The fibroblast growth factor dropped significantly 1 h following the first cryo-session, yet irisin remained statistically unchanged. The similar tendency was maintained after the whole procedure, still the range of changes was smaller. In the CRY group, an elevated uptake of tryptophan and valine noted in response to the whole intervention, could have induced a significant decrease of fasting glucose concentration (the adjusted effect small and very likely -6%; Coefficient Interval: -10 to -2%). Overall, a 2-week volleyball training program supported by the whole body cryostimulation protocol resulted in an increase of growth factors and offset a decline of physical performance. Thus these procedure can be applied in professional sport during competition period, especially among those disciplines focusing on an explosive power and ability to concentrate.